Preference for ugly faces? —A cognitive study of attentional and memorial biases toward facial information among young females with facial dissatisfaction - Zhu, Lan; Zhou, Huan; Wang, Xiaogang; Ma, Xiao; Liu, Qiaolan (Frontiers in Psychology, 2022)
The dissatisfaction with appearance is one of the most important contributors to negative physical image among Chinese young females, notably contributing to a series of psychological and behavioral obstacles. By conducting behavioral and ERP experiments, this study illustrates the features of how young females in China with facial dissatisfaction process different-levels of facial informative attractiveness respectively. Experiments 1 and 2 are behavioral experiments, using the dot-probe paradigm to explore the subject's attentional bias and components of facial information. The results showed that, whether the face image is presented above or below the threshold, young females with facial dissatisfaction exhibited vigilance towards low-attractive images and attention avoidance towards both low- and highly attractive ones. The control group showed difficulty in getting rid of the attention of the highly attractive face images. Experiments 3 and 4 are ERP experiments, using the recall-recognizing paradigm to explore the differences in subjects’ EEG components during face recall and recognizing stages. The study found that young females with facial dissatisfaction exhibited a preference for low-attractive images at both the acquainting and recognizing stages with higher P1, N170, P2, and N300 induced by low-attractive faces, while the control group preferred highly attractive faces. In conclusion, young females with facial dissatisfaction tend to pay attention and conduct memory processing encountering low-attractive faces.